2010
DOI: 10.1016/j.neulet.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Escherichia coli infection alters glial, cytokine, and neuronal gene expression in response to acute amphetamine in adolescent rats

Abstract: Neonatal bacterial infection in rats alters the responses to a variety of subsequent challenges later in life. Here we explored the effects of neonatal bacterial infection on a subsequent drug challenge during adolescence, using administration of the psychostimulant amphetamine. Male rat pups were injected on postnatal day 4 (P4) with live Escherichia coli (E. coli) or PBS vehicle, and then received amphetamine (15 mg/kg) or saline on P40. Quantitative RT-PCR was performed on micropunches taken from medial pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…For example, there is strong evidence correlating early CNS infection with the development of schizophrenia (Suvisaari, Mautemps et al 2003). Infections early in life can alter cytokine expression and glial activation in response to a subsequent immune challenge in adulthood (Bland, Beckley et al 2010), and a neonatal Escherichia coli infection has been shown to impair memory formation in adulthood in the presence of a subsequent immune challenge with LPS (Bilbo and Schwarz 2009). …”
Section: The Hiv-1tg Rat As a Model Of Neurohivmentioning
confidence: 99%
“…For example, there is strong evidence correlating early CNS infection with the development of schizophrenia (Suvisaari, Mautemps et al 2003). Infections early in life can alter cytokine expression and glial activation in response to a subsequent immune challenge in adulthood (Bland, Beckley et al 2010), and a neonatal Escherichia coli infection has been shown to impair memory formation in adulthood in the presence of a subsequent immune challenge with LPS (Bilbo and Schwarz 2009). …”
Section: The Hiv-1tg Rat As a Model Of Neurohivmentioning
confidence: 99%
“…Earlier work by Auten et al and preliminary data collected by the Bilbo lab found that exposure to air pollutants during the perinatal periods provoked an increase in cytokine expression in the fetal lung, brain, and placenta (33,34) .…”
Section: Discussionmentioning
confidence: 92%
“…Glial-neuronal signaling may also be a key mechanism that influences long-term changes following early immune challenge as postnatal exposure to E.coli infections has been shown to lead to immediate and long-term changes in microglia [35] . Certainly, microglia are emerging as a key regulator of CNS development and in particular, evidence is building that sex differences in microglia during early postnatal life may contribute to long-term sex differences in brain function.…”
Section: Discussionmentioning
confidence: 99%